Finacial Statemen Anaylisis to Assess Financial Performance PT. Ultrajaya Milk Industri & Trading Company TBK - Pasaribu, Ayu Ashari; Ismail, Muhammad; Dwita, Handriyani (LPPPIPublishing, 2025)
Financial Performance Assessment is based on increased sales. It can be reflected i n a report, a report describing the progress of the company's financial performance in a certain period. Such reports are commonly called financial statements. In orde r for financial statements to be meaningful to the interested parties it is necessary t o analyze the relationship of the posts in the financial statements are often called fi nancial statement analysis. The purpose of this study is to know how the financial performance of PT. Based on the analysis of liquidity ratio, solvency, activity and profitability. The data analysis method used is descriptive quantitative method usin g liquidity ratio measurement, solvency, activity and profitability. Based on the ov erall liquidity ratio, the company is in good condition except for cash ratio in 2022, although over the period of 2021-2023 fluctuates. Based on the sovency ratio of t he company's state in solvable position, because the company's capital is in suffici ent state to guarantee the debt given by the creditors. Based on the overall activity ratio is quite good. Based on the overall profitability ratio of the company is in a b ad position.